Reducing hospital acquired Clostridium difficile associated diarrhoea in an acute care facility - Costello, Dan (International Journal of Infection Control, 2007)
Hospital acquired Clostridium difficile associated diarrhoea (CDAD) was determined to be a longstanding historical concern at Nanaimo Regional General Hospital, with an infection rate nearly double the Canadian national average for similar sized facilities. During 2004/2005, a significant outbreak of CDAD fuelled an urgent response. The facilities, Infection Prevention & Control (IP&C) program deficiencies, and organizational culture issues were considered as strategies for improvement were contemplated. The multifaceted programmatic approach and partnerships with key stakeholders and patrons were instrumental in successfully reducing nosocomial CDAD and sustaining this low rate. The timeline for this initiative was 18 months beginning in July, 2005, with evaluation completed in December, 2006.